Heart rate variability and electrocardiographic parameters predictive of arrhythmias in dogs with stage iv chronic kidney disease undergoing intermittent haemodialysis - Alfonso, Angélica [UNESP]; Le Sueur, André N. V. [UNESP]; Geraldes, Silvano S. [UNESP]; Guimarães-Okamoto, Priscylla T. C. [UNESP]; Tsunemi, Miriam H. [UNESP]; Santana, Daniela F. [UNESP]; Ribeiro, Victor R. F. [UNESP]; Melchert, Alessandra [UNESP]; Chiacchio, Simone B. [UNESP]; Lourenço, Maria Lucia G. [UNESP] (MDPI, 2020)
Intermittent haemodialysis (IHD) is used in dogs with chronic kidney disease (CKD) to reduce azotaemia. Monitoring the cardiovascular system plays an important role in this treatment to detect cardiovascular repercussions. Heart rate variability (HRV) and dispersions of the QT interval and P wave are important markers for mortality risk in humans. This study aimed to describe the time-domain and frequency-domain heart rate variability indexes, P and QT dispersions and electrocardiographic alterations observed in dogs with Stage IV CKD undergoing IHD. Thirty dogs of both sexes, of varying ages and breeds, and weighing between 15 and 30 kg were used. Animals were divided into three groups, control (10 healthy dogs), clinical treatment (10 dogs with CKD IV submitted to clinical treatment twice a week) and IHD (10 dogs with CKD IV submitted to clinical treatment and to dialysis treatment with intermittent haemodialysis twice a week). Clinical, laboratory, HRV indexes and electrocardiographic parameters, as well as QT and P-wave dispersions, were assessed in both CKD groups, prior to and after the end of each clinical treatment/IHD session during the first three sessions. Dogs with CKD IV undergoing IHD had clinically important electrolyte imbalances, primarily hypokalaemia, and pertinent electrocardiographic findings, such as the occurrence of supraventricular arrhythmias and increases in possible predictive parameters for arrhythmias. In spite of these observations, HRV indexes were better in animals undergoing haemodialysis and, in addition, IHD was more effective at reducing levels of creatinine, urea and phosphorus compared to intravenous fluid therapy treatment.
Keywords: Canine; Cardiology; Electrocardiogram; Nephrology